Programming - Moir, I.
The following training program is designed for a weightlifter who is seventeen to eighteen years of age and has three years training experience. The program has five components: 1.Yearly training plan showing Individual cycles of varying duration between scheduled competitions 2.Volume and Intensity plan for individual cycles and phases within the cycles 3.Exercise Schedules 4.Weekly training schedules 5.Analysis of weekly tonnage